Teaching-learning of remote sensing at UNESP-FE Ilha Solteira: A proposal based on the previous knowledge of academics - Silva , Helio Ricardo; Marques , Artur Pantoja; Romero, Cristhy Willy da Silva (Seven Editora, 2023)
The present work aims to present the results of the use of the teaching-learning techniques Posters in Group (CG) and Group of Observation versus Group of Verbalization (GOxGV), compared to the expository technique, applied in the disciplines that use remote sensing in Agronomy and Biological Sciences. The techniques in which the university students learned acting (CG) and (GOxGV), were applied between 1998 and 2015 and compared to the traditional expository technique used until 1997. It was found that teaching-learning was more efficient and pleasant than in the expository technique. In addition, the teacher had immediate feedback on student learning. DOI:https://doi.org/10.56238/ptoketheeducati-033